Miskonsepsi Siswa dalam Menyelesaikan Soal Cerita Pemecahan Masalah Matematika Materi Perbandingan dan Skala Kelas V SD Negeri Sowan Kidul Kabupaten Jepara - Galih Retna Utami; Fajar Cahyadi; Husni Wakhyudin (STKIP Andi Matappa Pangkep, 2021)
The aim to be achieved is to find out the students' misconceptions in solving the math story problem of the fifth grade students of SD Negeri Sowan Kidul, Jepara Regency. This research uses descriptive qualitative research. The subjects of this study were the fifth grade students of SDN Sowan Kidul totaling 25 students. The data collection methods were students' ability tests, teacher interviews and student questionnaires. The data validity test was done by triangulation. Data analysis techniques in this study used data reduction, data presentation, and drawing conclusions. The results of the analysis obtained were 1) 57.36% of students experienced translation misconceptions; 2) 72.12% of students experienced misconceptions of concepts 3) 79.12% of students experienced arithmetic misconceptions; 4) 75.64% of students experienced misconception of signs; 5) 76.51% of students experienced a misconception of strategies.